2017
DOI: 10.1002/prep.201600125
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Decomposition Research on 1,5‐Diazabicyclo[3.1.0] Hexane (DABH) as a Potential Low‐toxic Liquid Hypergolic Propellant

Abstract: 1,5-Diazabicyclo[3.1.0] hexane (DABH) was found a potential hypergolic liquid propellant. The physical and energetic properties of DABH, 2-(dimethylamino) ethyl azide (DMAZ), and monomethyl hydrazine (MMH) were compared. The ignition delay time of DABH with nitrogen tetroxide was 1 ms, which was shorter than DMAZ and similar with MMH. The toxicology experiment showed that half lethal dose (LD 50 ) of DABH was 621.0 mg kg À1 , which sug-gested that DABH was promising to be used as low-toxic liquid propellant. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Thermal stability determined the practicable value of propellants. The thermal decomposition test was one of the reliable means to investigate the stability and energetic value [12]. Meanwhile, Arrhenius parameters determined from decomposition progress are of value because of the description of a complex series of reactions [13][14][15].…”
Section: Thermal Decomposition Properties By Dscmentioning
confidence: 99%
“…Thermal stability determined the practicable value of propellants. The thermal decomposition test was one of the reliable means to investigate the stability and energetic value [12]. Meanwhile, Arrhenius parameters determined from decomposition progress are of value because of the description of a complex series of reactions [13][14][15].…”
Section: Thermal Decomposition Properties By Dscmentioning
confidence: 99%
“…20 Due to its high enthalpy of formation and low toxicity, DABH was found to be a promising liquid propellant as an alternative to toxic hydrazine derivatives. 21,22 The possibility of using solid PDABH as a high-energy material is yet to be explored and, therefore, the thermochemical properties of DABHs and other diaziridine derivatives are critical to the successful modeling of diaziridine-based high-energy materials. Nevertheless, to our knowledge, no experimental study of the enthalpy of formation of any diaziridine has been reported so far.…”
Section: Introductionmentioning
confidence: 99%